Dry powder cationic lipopolymeric nanomicelle inhalation for targeted delivery of antitubercular drug to alveolar macrophage - Vadakkan MV (Dove Medical Press, 2013)
Mithun Varghese Vadakkan,1 K Annapoorna,2 KC Sivakumar,3 Sathish Mundayoor,2 GS Vinod Kumar1 1Chemical Biology, 2Mycobacterium Research Group, 3Bioinformatics Facility, Rajiv Gandhi Centre for Biotechnology, Thiruvananthapuram, Kerala, India Abstract: Excipients having self-assembling properties are less explored in the field of dry powder inhalation (DPI) technology. An amphiphilic lipopolymer system was developed using stearic acid (SA) and branched polyethyleneimine (BPEI) (1800 Dalton), at different proportions by covalent conjugation. A molecular dynamic (MD) simulation tool was employed for predicting the carrier behavior in a polar in vivo condition. The structural characterization was carried out using nuclear magnetic resonance spectroscopy (NMR) and Fourier transform infrared (FTIR) spectroscopy. The physical nature of the lipopolymer was analyzed by differential scanning calorimetry. Determination of zeta potential and diameter of the micelles showed existence of cationic particles in the nano size range when a lower number of primary amino groups of BPEI was grafted with SA. The rifampicin (RIF)-loaded lipopolymer was also formulated further into spray-dried microparticles. Powder X-ray diffraction (PXRD) studies revealed that the RIF API (active pharmaceutical ingredient) exists as molecular dispersion in spray-dried microparticles. Topological analysis of the spray-dried nanomicelle was carried out using scanning electron microscopy (SEM). A large population of the drug-carrying particles were found to be under the inhalable size range (fine particle fraction 67.88% ± 3%). In vitro drug release kinetics from spray-dried nanomicelles were carried out at lung fluid pH. Keywords: molecular dynamics, dry powder inhalation, pulmonary tuberculosis, nanomicelle, lipopolymer, rifampicin